Birds Eye 5-70, 4-14 November 1970. - Freeman,R. F.; Agee,H. J. (1971)
BIRDS EYE 5-70 was a regularly scheduled Arctic Ocean ice reconnaissance mission covering the North American sector of the Arctic Ocean including Baffin Bay and Davis Strait from 4 to 14 November 1970. An airborne laser profilometer system was used continuously over the Arctic Ocean to obtain ice surface profiles. Ice observations were collected under daylight conditions in low latitudes and in twilight or moonlight in high latitudes. (Author)